A study of variables in gastrointestinal stromal tumor: surgical experience at a single institute - Shah, Udit Jaydeep; Akruwala, Sushil D.; Sharma, Vidhyasagar M.; Pipalia, Manubhai V. (International Surgery Journal, 2019)
Background: Gastrointestinal stromal tumors (GIST) have been recognized as a biologically distinctive tumor type, different from the smooth muscle and neural tumors of the gastrointestinal tract. They constitute majority of the gastrointestinal mesenchymal tumors of the gastrointestinal tract and are considered to be refractory to conventional chemotherapy or radiation. Surgery remains the mainstay of primary tumor management of GIST. Methods: This was a cross sectional study of the diagnosis, management and clinical outcome of cases diagnosed with GIST of the gastrointestinal tract from a teaching institute in a single year and a comparison of findings with previously published cases. Study included patients newly diagnosed with GIST and managed in department of general surgery from 10 April 2018 to 31 March 2019. Results: Most patients were of age group 60-69 years with an almost equal incidence among males and females. Stomach and small bowel were found to be the commonest sites with an equal distribution of 45.45% with an average tumor size of 5 cms. Conclusions: Surgical treatment remains the main stay of management for the GIST, depending on the location, staging and metastasis. Staging laparoscopy may be done to assess respectability as peritoneal deposits can be missed by CT scan. Immunohistochemistry is mandatory in defining GIST.